Optical properties and plasmonic states in two-dimensional alpha lead oxide systems: a density-functional study. (8th February 2019) - Kurniawan, Yudhi; Muhammady, Shibghatullah; Widita, Rena; Darma, Yudi
Abstract: We study electronic and optical properties of the two-dimensional (2D) systems of monolayer and bilayer alpha lead oxide ( α -PbO) systems. The plane-wave method within the generalized gradient approximation is employed. We revisit the properties of bulk α -PbO system as the references. The indirect minimum bandgaps ( E g ) of the bulk (1.645 eV, 0.2Δ → M) and bilayer systems (1.969 eV, 0.1Σ → Γ) become the direct E g in the monolayer system (2.53 eV, Γ → Γ). The E g mainly come from Pb 6 p and O 2 p orbital states in the conduction and valence bands, respectively. The presence of valence band maximum at 0.2Δ and 0.1Σ points in the bulk and bilayer systems, respectively is induced by the Γ-point Mexican-hat dispersion, which disappears in the monolayer system. Furthermore, we find the strong van Hove singularity, which mainly comes from O 2 p states, in the monolayer system. The optical properties show that the optical dichroism and dielectric constant ( ε 0 ) of the 2D systems are higher and lower, respectively, than that of the bulk system. From the electron-energy-loss functions, the transformation of the bulk into the 2D systems can tune the energy levels of plasmonic states. We emphasize that the visible-region plasmonic states enhance in the monolayer system compared to that of the bulk system. This study opens the potential application of the 2D α -PbO systems in low-energy plasmonic devices.